Cerebellar modulation of anxiety behavior - Chin, Pei Wern (Nanyang Technological University, 2023)
The cerebellum is traditionally known for its role in coordinating motor functions. Evidence now indicate that the cerebellum is also involved in an array of non-motor functions, such as anxiety. Findings from a recent study suggest that an anxiety locus in the cerebellar cortex is located in lobule VII of the vermis. To determine whether lobule VII is indeed a topographical locus for anxiety behavior, I photostimulated lobule VII molecular layer interneurons via optogenetics and observed an increase in anxiety behavior in the elevated zero maze. This anxiogenic effect was observed in male mice but not female mice, indicating that lobule VII is a sex-specific anxiety locus in the cerebellum. I next investigated whether serotonin (5-HT) – one of the most-studied neuromodulator transmitters in anxiety – is also involved in cerebellar anxiety behavior. I measured 5-HT levels by expressing a fluorescent sensor for 5-HT in lobule VII of male mice and performed fiber photometry recordings during anxiety behavior. My results indicate that 5-HT levels in lobule VII increase when mice are less anxious and decrease when mice are more anxious. To determine whether serotonergic input into lobule VII is sufficient and necessary to regulate cerebellar anxiety behavior, I photostimulated and photoinhibited lobule VII 5-HT terminals in male mice during anxiety tests. Mice exhibited anxiolytic behavior upon photostimulating lobule VII 5-HT terminals, whereas anxiogenic behavior was observed upon photoinhibition of lobule VII 5-HT terminals. Taken together, my findings suggest that (1) lobule VII is a sex-specific topographical locus in male mice for anxiety behavior, and that (2) 5-HT input into this anxiety locus is necessary and sufficient to regulate anxiety behavior in a bidirectional manner. These findings represent a pivotal step toward understanding how the cerebellum regulates anxiety behavior and provide new evidence for a functional connection between the cerebellum and the 5-HT system in the anxiety circuit.